1991
DOI: 10.1002/1097-0142(19910701)68:1<48::aid-cncr2820680110>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Improved treatment results in boys with overt testicular relapse during or shortly after initial therapy for acute lymphoblastic leukemia. A pediatric oncology group study

Abstract: Boys with acute lymphoblastic leukemia (ALL) who have overt testicular relapse (OTR) during initial continuation chemotherapy or within 6 months thereafter have poor outcomes, with long-term survival similar to patients with marrow relapse during treatment. In April 1983, the Pediatric Oncology Group (POG) adopted for these patients an intensive treatment protocol (POG 8303) consisting of a four-drug systemic reinduction (prednisone, vincristine, daunorubicin, and asparaginase), a brief intensive consolidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The major impact of isolated testicular relapse (ITR) is the high incidence of subsequent systemic relapse, though this appears to be directly influenced by length of first clinical remission (CR1). [18][19][20][21][22][23] In POG 8304 (1983)(1984)(1985)(1986)(1987)(1988)(1989), the overall 4-year event-free survival (EFS) among males with occult testicular relapse at completion of therapy was 53 ± 8%, compared to 84 ± 10% for males with late overt ITR (6 months or greater following completion of therapy). 18,19 A more recent analysis of the CCG database (CCG 1881, CCG 1882, CCG 1901, CCG 1883, CCG 1922, unpublished results) showed a trend to poorer outcome for those with CR1< 18 months versus >18 months (5-year EFS 43% vs. 61%, respectively), though numbers are small and do not reach statistical significance.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The major impact of isolated testicular relapse (ITR) is the high incidence of subsequent systemic relapse, though this appears to be directly influenced by length of first clinical remission (CR1). [18][19][20][21][22][23] In POG 8304 (1983)(1984)(1985)(1986)(1987)(1988)(1989), the overall 4-year event-free survival (EFS) among males with occult testicular relapse at completion of therapy was 53 ± 8%, compared to 84 ± 10% for males with late overt ITR (6 months or greater following completion of therapy). 18,19 A more recent analysis of the CCG database (CCG 1881, CCG 1882, CCG 1901, CCG 1883, CCG 1922, unpublished results) showed a trend to poorer outcome for those with CR1< 18 months versus >18 months (5-year EFS 43% vs. 61%, respectively), though numbers are small and do not reach statistical significance.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand , Buchanan et al 2 studied the outcome of 38 boys who had overt testicular relapse of ALL and reported that, after clinical remission, 22 cases had another relapse involving the bone marrow in 12, CNS in five, testes in two, retroperitoneal in one, prostate in one, and eye in one. In another paper, Quien et al 3 has reported a case of a 67-year-old male with primary extramedullary ANLL of the prostate.…”
Section: Discussionmentioning
confidence: 99%
“…Outcome after short CR1 duration (<12–18 months) is very poor, as is the prognosis for individuals who are unable to achieve a second remission. Those with isolated extramedullary relapse fair better than those with marrow relapse [48,49]. …”
Section: Acute Lymphoblastic Leukemia (All)mentioning
confidence: 99%